Studi Teoritis Penggunaan Derivasi Asam Siano sebagai Akseptor Elektron dalam Pelargonidin sebagai Senyawa Pewarna Sel Surya Sensitasi - Muhamad Imam Muslim; Sudarlin Sudarlin (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
The theoretical study of the use of cyano acid derivatives as electron acceptor groups in pelargonidin as a dye compound in sensitized solar cells (DSSC) was successfully carried out. Theoretical study was carried out with the purpose to determine the effect modification of the addition of cyanoacrylic benzothiadiazole, cyanoacrylate, cyanovinyl, and cyanocynamic as electron acceptors to the characteristics of pelargonidin as dye DSSC. The effect of modification is based on the parameters of bond length, spectra, molecular electron density, light harvesting efficiency (LHE), (VRP), and HOMO-LUMO energy. The molecular structure created using the Avogadro program, then optimized by DFT/TDDFT method using a base set 6.311G *. Based on the results of research on pelargonidin-benzothiadiazole cyanoacrylate is a better modification when compared with pelargonidin without modification or pelargonidin modified with other cyano acids. This modification is better modification based on parameters molecular electron density, HOMO-LUMO energy, (VRP), bond lengths, and spectra. Pelargonidin-benzothiadiazole cyanoacrylic electron density in LUMO conditions centred in benzothiadiazole cyanoacrylic, HOMO and LUMO energy of dye is -4.97856 eV & -2,56731 eV, VRP value 0.439, bond lengths 1.936 Å, and spectra at wavelength 393.14 nm & 377.09 nm. Based on the light harvesting efficiency (LHE), pelargonidin without modification is the best modification with an LHE value 0.820.